2015
DOI: 10.1039/c5ta01977j
|View full text |Cite
|
Sign up to set email alerts
|

Enabling a high capacity and long cycle life for nano-Si anodes by building a stable solid interface with a Li+-conducting polymer

Abstract: Great efforts have been devoted to developing nano-Si anodes for next-generation lithium ion batteries (LIBs); however, the reversible capacity and cycling stability of all Si anodes developed so far still need to be improved for battery applications. In this work, we propose a new strategy to develop a cycling-stable Si anode by embedding nano-Si particles into a Li + -conductive polymer matrix, in which a stable Si/polymer interface is established to avoid the contact of the Si surface with the electrolyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…4 Furthermore, Si-based materials having different structures and compositions have also been investi-gated as a means of preventing this structural damage. [5][6][7][8][9][10][11][12][13][14] For example, Si nanomaterials, including nanoparticles, 5,6 nanowires 7 and nanotubes, 8 have been reported to exhibit effective capacity retention, especially in the presence of an active carbon matrix. Amorphous Si also shows promise in this regard, 9,10 unlike crystalline Si, which is prone to high stresses and associated cracking.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, Si-based materials having different structures and compositions have also been investi-gated as a means of preventing this structural damage. [5][6][7][8][9][10][11][12][13][14] For example, Si nanomaterials, including nanoparticles, 5,6 nanowires 7 and nanotubes, 8 have been reported to exhibit effective capacity retention, especially in the presence of an active carbon matrix. Amorphous Si also shows promise in this regard, 9,10 unlike crystalline Si, which is prone to high stresses and associated cracking.…”
Section: Introductionmentioning
confidence: 99%
“…6c), the broad reduction peak between 0.5 V and 1.1 V can be assigned to the decomposition of electrolyte, which leads to the formation of SEI film [41]. The disappearance of this peak in the subsequent cycles suggests the formation of a stable SEI film on the surface of active material at the first cycle [42,43].…”
Section: Resultsmentioning
confidence: 95%
“…[ 284 ] Subsequently, their group embedded Si nanoparticles into a Li + ‐conductive polymer matrix (polybithiophene) to avoid the contact of the Si surface with electrolyte and to buffer the volume change by ball‐milling ( Figure a). [ 285 ] The as‐prepared nano‐Si/polybithiophene electrodes exhibited a high Li‐storage capacity of about 2900 mA h g −1 and an excellent cyclability with a capacity retention of about 1000 mA h g −1 over 1000 cycles at 12 A g −1 . Komaba reported that a partially NaOH‐neutralized poly(acrylic acid) provides the moderate porous structure inside the composite electrodes when was examined as a binder for Si‐based anode electrodes, exhibiting an enhanced capacity retention (Figure 23b).…”
Section: Designing Protective and Conductive Phases For Si Anodementioning
confidence: 99%